Implementasi Nilai-Nilai Islam Dalam Meningkatkan Kualitas Pelayanan Pada Pelanggan Pendidikan - Nur, Muhammad Amin (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Currently we are in an era of quality, every consumer or customer of both goods and services expect quality. Institutions that rely on service quality, people will be increasingly in demand as customers. Instead institutionthat ignores its customers quality service will be abandoned. Customer education is always to be aware of the needs and expectations include the students and their parents who feel the direct impact of education services. One indicator of the low quality of education is the low level of trust and the level of customer satisfaction (learners and their parents) toeducational services. The low quality of educational services to customers often happens because the pengalola institutions ignore the universal values that the values of Islam. Now it’s time especially educational institutions of Islamic education institutions to review their Islamic values and implement them in improving the quality of service to its customers, in order to remain prosperous Islamic educational institutions and competitive in the global competition intensifis.Keywords: Islamic Values, Quality Service, Customer Education